Effects of Shikonin on the Functions of Myeloid Dendritic Cells in a Mouse Model of Severe Aplastic Anemia - Mengying Zheng; Bingnan Liu; Yuanyuan Shao; Luogang Hua; Rong Fu; Huaquan Wang; Ting Wang; Weiwei Qi; Zonghong Shao; Chunyan Liu (Mediators of Inflammation)
This study is aimed at investigating the effects of shikonin, a pyruvate kinase M2 (PKM2) inhibitor, on the functions of myeloid dendritic cells (mDCs) in a mouse model of severe aplastic anemia (AA) generated by total body irradiation and lymphocyte infusion. Flow cytometry and qPCR were used to determine the proportions of PKM2+ mDCs and other immune indicators in the AA mice. Glucose consumption level, pyruvate generation level, and ATP content were used to determine the level of glycolytic metabolism in the mDCs. The survival rates of AA mice were evaluated after the administration of shikonin or the immunosuppressive agent cyclosporin A. The AA mice displayed pancytopenia, decreased CD4+/CD8+ cell ratio, increased perforin and granzyme levels in CD8+ cells, increased costimulatory CD80 and CD86 expressions, and inadequate regulatory T cell number. In vivo animal experiments showed that the shikonin-mediated inhibition of the PKM2 expression in mice was associated with high survival rates. In addition, the administration of cyclosporin A or shikonin decreased the expression of cytotoxic molecules and costimulatory CD80 and CD86 on CD8+ cells. Taken together, the results of this study indicated that shikonin could inhibit the activation and proliferation of mDCs as well as the activation of downstream cytotoxic T cells by reducing the PKM2 level in mDCs.